Relationship between regional hepatic glucose metabolism and regional distribution of hepatic fat. Issue 3 (March 2019) - Dunford, Alexander; Keramida, Georgia; Singh, Nitasha; Aplin, Mark; Peters, A. Michael
Abstract : Aim: Hepatic steatosis is associated with insulin resistance and hyperinsulinaemia. Insulin stimulates hepatic glucokinase, even in insulin resistance, so hepatic glucose uptake is increased in hepatic steatosis. The study hypothesis was that hepatic glucose uptake is also influenced locally by fat, the hepatic distribution of which is heterogeneous. Patients and methods: Sixty patients undergoing PET/CT using fluorine-18-fluorodeoxyglucose ( 18 F-FDG) had dynamic imaging of the liver for 30 min after injection before undergoing whole-body PET/CT at 60 min after injection. Hepatic 18 F-FDG uptake was measured using Gjedde–Patlak–Rutland graphical analysis. Plot gradient ( K i ), which represents hepatic blood clearance of 18 F-FDG to phosphorylation, was normalized to intercept [ V (0)], which represents the hepatic 18 F-FDG distribution volume. The 60 min computed tomography (CT) was co-registered on to each of the 30 dynamic PET frames. This failed in 20 patients. A further seven patients with lymphoma and three with hepatic metastases were excluded. Within transaxial sections, the liver was divided into small regions of interest (ROIs) of 5×5 pixels each in sections of 5 mm (range: 118–586 ROIs/liver). CT density and K i / V (0) were measured in each ROI. Results: Throughout the 25-pixel ROIs in the individual liver, CT density and K i / V (0) showed a significant negative correlation in 15/30 patients. It was significantly positive in only three ( P =0.01). In some patients, parametric imaging showed regional concordance between K i / V (0) and hepatic fat, identified as reduced CT density. Conclusion: In addition to systemic influences, hepatic glucose uptake is regionally linked to the distribution of hepatic fat. Increased metabolism could be the cause or result of local fat deposition.